THE APORIAS OF THE VICIOUS CIRCLE IN A POLITICAL BEGINNING: REFLECTIONS ON H. ARENDT'S THOUGHTS ON THE FOUNDATION OF A POLITY. - Zhang Yan; Gao Song (Problems / Problemos, 2018)
Modern revolution as the beginning of founding a new political order has to confront the vicious circle inhered in all beginnings: in so far as it is the beginning, where does its principle come from? Or, if there is no principle, how could the beginning establish one? Set in the context of modern political experience, the aporia is equal to the problem of how modern politics to be self-grounded or how to reestablish political authority in modernity? By an exploration into the relevant writings of Hannah Arendt, the article tries to investigate the vicious circle of beginning and principle in the political realm, and to point out that Arendt has told a story about the mutual generating of beginning and principle, turning the so-called vicious circle into a hermeneutic circle, in which those implicit principles become explicit through the performance of founding actions.